การศึกษากับการพัฒนาปัญญาประดิษฐ์ - วิโรจโน (นิลเพ็ชร), พระมหาวิรุธ; (อูธ จันทร์ทุม), พระครูสุธีวรสาร; ปโยโค, พระมหาจิรายุทธ (วารสาร มมร ยศสุนทรปริทรรศน์, 2024)
In the 21 st century, artificial intelligence is rapidly revolutionizing the educational landscape. AI presents unprecedented opportunities to enhance teaching, assessment, and educational management, with the potential to transform our methods of learning and teaching completely. It allows for personalized learning tailored to the needs and strengths of each individual. AI systems can analyze student data to identify areas for improvement and create customized learning plans. In this way, AI can help learners progress at their own pace and achieve their full potential. AI can be used to assess students' knowledge and skills more efficiently and accurately. AI systems can provide real-time feedback and pinpoint areas needing improvement. Moreover, AI can reduce bias in assessments by removing human factors from the process. AI can help manage education more effectively. Additionally, AI can reduce administrative tasks, freeing up teachers to have more time to teach. AI creates new opportunities for lifelong learning. AI-powered learning platforms enable learners of all ages to access diverse learning content anytime, anywhere.